MODERNIOSIOS EPISTEMOLOGIJOS SOLIPSIZMAS EX PRINCIPIO INTERNO. - Šaulauskas, Marius Povilas (Problems / Problemos, 2012)
Epistemology serves as a crucial constituent of modern philosophy. Theory of knowledge, in contrast to axiological and ontological theorization, provides the ultimate framework underpinning the problematic whole of philosophical inquiry. Therefore, epistemic claims of the philosophical discourse should be articulated in terms of metaphilosophical reflection not only by reducing scrutinized problematics into the heuristic potential of philosophical analysis sui generis, but also by grounding such a potential in terms of its necessity, certainty and uniqueness. Metaphilosophical self-founding of the philosophical modernity dwells on an imperative identification of the epistemic and epistemological ego: knowledge posits itself only by providing its own procedural principals and grounds of justification. Hence the unsurpassable primacy of reflective epistemology, and by the same token the urgent necessity to avoid solipsism transforming the enterprise of modern epistemology into the agneological discourse par excellence. Modern epistemological metaphilosophy, in the wake of solipsism, turns into agneology ex principio interno: epistemologically grounded philosophy unfolds not as a fortification of knowledge and truth, but as the unremitting search after the amelioration of ignorance and falsehood.